The issue of make-up water in the network regulation and new heat production technologies – proposal for changes to the network regulation - Bujalski, Wojciech; Niemyjski, Olgierd; Chorzelski, Maciej (Instal, 2024)
The operation of district heating systems is regulated by the so-called Network Ordinance of 2007. Since it entered into force (17 years ago), district heating technology has advanced enormously, and some of the provisions contained therein are out of step with modern technology. The authors critically analysed the regulation’s requirements for constructing treatment stations and make-up facilities in district heating systems for new heat sources to be connected to them. They proposed a modification of the regulation